You need to know that e^(a+b) = (e^a)*(e^b).
So...
e^(1+lnx) =
e^1 * e^lnx
Then you need to know that e and ln are inverse functions, so e^lnx = x:
e^1 * e^lnx =
e * x
2007-06-19 09:00:01
·
answer #1
·
answered by McFate 7
·
1⤊
1⤋
It is not an equation - no equal sign. You can simplify it:
e^(1+lnx)=e^1 * e^lnx = ex
2007-06-19 09:01:02
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
This can be simplified down to:
(e^1)*(e^lnx)
because you add exponents when you multiply. This can be simplified further:
(e^1)*x
because e^lnx = x
2007-06-19 09:01:58
·
answer #3
·
answered by Math Stud 3
·
0⤊
0⤋
break it into a series equivalent.
or break it into its components.
if i remember e^(a+b) = e^a * e^b
which would make this
(e^1) * (e^lnx)
e^1 = e
e^lnx = x (i believe)
which would make this x*e
lemme know
jean_has_Cats@yahoo.com
2007-06-19 09:01:28
·
answer #4
·
answered by jean_has_cats 2
·
0⤊
0⤋
This is not an equation. This is an expression to be simplified.
e^(1 + ln x)
= (e^1)( e^(ln x)) because a^(m + n) = (a^m)(a^n)
= (e)(x) because a^1 = a and e^(ln a) = a.
Answer: ex or xe (the product of x e and x)
2007-06-19 09:20:22
·
answer #5
·
answered by mathjoe 3
·
0⤊
0⤋
Remember that the function's domain is restricted!!!!! For all x>0, it is the function f(x) = e*x, as the previous posts said. But for x<0, the function becomes imaginary.
2007-06-19 09:04:07
·
answer #6
·
answered by J Z 4
·
0⤊
0⤋
review your exponent rules
e^(a+b) = e^a*e^b
so e^(1+lnx) = e^1*e^lnx = e*x
2007-06-19 09:00:16
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
You can use your exponential rules:
e * e^lnx => e * x
2007-06-19 09:00:28
·
answer #8
·
answered by sharky.mark 4
·
0⤊
0⤋